Evaluation of Physical Quality Test, Proximate Test, and Production Performance Test of Sorghum and Corn Substitute Pellets with Enzymatic Treatment - Mahanani, Agni Ayudha; Khatifah, Khatifah (Jurnal Agripet, 2025)
The purpose of this study is to determine the effect of enzymatic treatment on the physical quality test, proximate test, and performance test of pellets given enzymatic treatment on sorghum and corn. This study was conducted at the Integrated Animal Husbandry Laboratory, The University of West Sulawesi, which included physical quality tests and proximate tests. The treatment in the first stage of the study, namely, enzymatic treatment on sorghum at concentrations of 0.25%, 0.50%, 0.75%, 1%, and 0% (control) cellulase enzyme, was tested to assess the effect of increasing nutrition and decreasing crude fiber. The second stage was the preparation of feed to see the quality of the pellet test with the arrangement of treatments P0: 100% corn and 0% enzymatic sorghum, P1: 25% corn and 75% enzymatic sorghum, P2: 50% corn and 50% enzymatic sorghum, P3: 75% corn and 25% enzymatic sorghum, P4: 0% corn and 100% enzymatic sorghum. This study used a Completely Randomized Design (CRD) method with research treatments consisting of 5 treatments and 5 replications. The results of the study in the first stage can be concluded that the addition of cellulase-based enzymes to sorghum can increase crude protein and can reduce the content of crude fiber, NDF, ADF, hemicellulose. The SE2 treatment and in the second stage the treatment showed the best results based on the combination of all tests was P4 (100% enzymatic sorghum), because it provides more durable physical and organoleptic quality performance.